Multi-omics analyses of the heterogenous immune microenvironment in triple-negative breast cancer implicate UQCRFS1 potentiates tumor progression - Yuhui Tang; Aiqi Xu; Zhongbiao Xu; Jindong Xie; Wei Huang; Liulu Zhang; Yitian Chen; Lu Yang; Shasha Du; Kun Wang (Experimental Hematology & Oncology)
Abstract Background Triple-negative breast cancer (TNBC) is commonly characterized by high-grade and aggressive features, resulting in an augmented likelihood of distant metastasis and inferior prognosis for patients. Tumor immune microenvironment (TME) has been recently considered to be tightly correlated with tumor progression and immunotherapy response. However, the actual heterogenous TME within TNBC remains more explorations. Methods The thorough analyses of different cell types within TME were conducted on the self-tested single-cell RNA sequencing dataset which contained nine TNBC treatment-naïve patients, including subclusters classification, CellChat algorithm, transcription factors (TFs) expression, pseudotime analysis and functional enrichment assay. The malignant epithelial cluster was confirmed by copy number variations analysis, and subsequently LASSO-Cox regression was carried out to establish a Malignant Cell Index (MCI) model on the basis of five crucial genes (BGN, SDC1, IMPDH2, SPINT1, and UQCRFS1), which was validated in several TNBC cohorts through Kaplan–Meier survival and immunotherapy response analyses. The public spatial transcriptome, proteome data and qRT-PCR, western blotting experiments were exploited to corroborate UQCRFS1 expression in RNA and protein levels. Additionally, functional experiments were implemented to unravel the impacts of UQCRFS1 on TNBC cells. Results The diverse subclusters of TME cells within TNBC were clarified to display distinct characteristics in cell–cell interactions, TFs expression, differentiation trajectory and functional pathways. Particularly, IL32high Treg imparted an essential effect on tumor evasion and predicted a worsened prognosis of TNBC patients. Furthermore, MCI model enabled to notify the inferior prognosis and immunotherapy resistance in TNBC. Ultimately, UQCRFS1 knockdown dampened the proliferative and migratory competence in vitro as well as tumor growth in vivo of TNBC cells. Conclusions Our study offers innovative perspectives on comprehending the heterogeneity within TME of TNBC, thereby facilitating the elucidation of TNBC biology and providing clinical recommendations for TNBC patients' prognosis, such as IL32high Treg infiltration, MCI evaluation, and UQCRFS1 expression.